Controls of Multiple Stressors on the Black Sea Fishery - Oguz, Temel (Frontiers in Marine Science, 2017)
Black Sea is one of the most severely degraded and exploited large marine ecosystems in the world. For the last 50 years after the depletion of large predatory fish stocks, anchovy (with the partial contribution of sprat) has been acting as the main top predator species and experienced a major stock collapse at the end of 1990s. After the collapse, eastern part of the southern Black Sea became the only region sustaining relatively high anchovy catch (400,000 tons) whereas the total catch within the rest of the sea was reduced to nearly its one-third. The lack of recovery of different fish stocks under a slow ecosystem rehabilitation may be attributed, on the one hand, to inappropriate management measures and the lack of harmonized fishery policy among the riparian countries. On the other hand, impacts of multiple stressors (eutrophication, alien species invasions, natural climatic variations) on the food web may contribute to resilience of the system toward its recovery. The overfishing/recovery problem therefore cannot be isolated from rehabilitation efforts devoted to the long-term chronic degradation of the food web structure, and alternative fishery-related management measures must be adopted as a part of a comprehensive ecosystem-based management strategy. The present study provides a data-driven ecosystem assessment, underlines the key environmental issues and threats, and points to the critical importance of holistic approach to resolve the fishery-ecosystem interactions. It also stresses the transboundary nature of the problem.